The Role of Institutional Pressures in Driving Internal and External Green Supply Chain Practices and Environmental Performance - Djoko Roespinoedji; Ryan Kurniawan; Ucu Nugraha; Noor H. Jabarullah (International Journal of Supply Chain Management, 2019)
The contribution of the present investigation is also extended to determine the impact of green supply chain practices in influencing organizational performance. Hence, the understanding drive from such comprehensive approach will aid the manufacturing sector of Malaysia to identify the contribution of local and international institutions’ pressures in affecting the success of Malaysian green supply chain methods. In this current research, we applied of Exploratory Factor Analysis (EFA) to discover the four factors are extracted by total twenty-nine items in which all items factor loadings are more noteworthy than 0.70. The results of structural equation modelling confirm that internal green supply chain practice and external green supply chain practice have significantly and positively influenced by institutional pressure. Furthermore, the outcomes of structural equation modelling also certify that, institutional pressure has a positive and significant impact on environmental performance. Finally, the outcomes more explained that internal green supply chain practices and external green supply chain practices have a positive and significant effect on environmental performance in manufacturing firms of Malaysia.